Long Non-coding RNA MSTRG.24008.1 Regulates the Regeneration of the Sciatic Nerve via the miR-331-3p–NLRP3/MAL Axis - Yin, Gang; Peng, Ying; Lin, Yaofa; Wang, Peilin; Li, Zhuoxuan; Wang, Renyuan; Lin, Haodong (Frontiers in Cell and Developmental Biology, 2021)
Peripheral nerve injury (PNI) is a common clinical problem, which can cause severe disability and dramatically affect a patient’s quality of life. Neural regeneration after PNI is a complex biological process that involves a variety of signaling pathways and genes. Emerging studies demonstrated that long noncoding RNAs (lncRNAs) were abnormally expressed after PNI and played pivotal roles in peripheral nerve regeneration. Based on the rat sciatic nerve injury model, we found that the expression levels of several lncRNAs were increased significantly in the sciatic nerve after injury. Software prediction prompted us to focus on one up-regulated lncRNA, MSTRG.24008.1. Dual-luciferase reporter assay, RNA pull-down assay and RNA interference approach verified that MSTRG.24008.1 regulated neuro regeneration via the miR-331-3p/nucleotide-binding oligomerization domain-like pyrin domain containing 3 (NLRP3)/myelin and lymphocyte protein (MAL) axis in vitro. Subsequently, we performed gastrocnemius muscle gravity and sciatic functional index experiments to evaluate the recovery of injured sciatic nerves after MSTRG.24008.1 siRNA interference in vivo. In conclusion, knockdown of MSTRG.24008.1 promotes the regeneration of the sciatic nerve via the miR-331-3p/NLRP3/MAL axis, which may provide a new strategy to evaluate and repair injured peripheral nerves clinically.